Peningkatan Kompetensi Dasar Menggambar Proyeksi dengan Metode Tutor Sebaya pada Siswa Kelas X Teknik Pemesinan 3 Semester 11 SMK N 2 Kebumen Tahun Pembelajaran 2014/2015 - Riyanto, Warnu (widiyanto, 2015)
The competence in drawing projection are still low. Therefore, there should be an attempt to resolve such matters. The use of the method of peer tutors can be an alternative on improving the competence in drawing projections. This research use class activities research. The outline of this research issue is whether the application of the method of learning tutorials peers can increase the competence in drawing a projection on the students of class X Engineering third of 2 Kebumen Vocation High School in school year 2014/2015? Based on the results of the research, the data that obtain with the method of peer tutors are able to increase the competence of students in drawing projections.